INVESTIGATING THE MODERATING ROLE OF AUTHORITARIAN LEADERSHIP IN THE RELATIONSHIP BETWEEN DIGITAL TRANSFORMATION AND JOB STRESS - Dr. Abbas Gatea Atiyah (Scholars Digest Publishing, 2023)
This study aimed to explore the obstacle posed by Digital Transformation and Authoritarian Leadership in weakening worker performance. Therefore, the hypotheses of the study were tested in one of the important institutions in the oil sector (the petroleum products distribution company in Thi-Qar Governorate). The test was conducted on a sample of (139) managers from all managerial levels in the company. The research model and its hypotheses were tested using SmartPLS. The results of the study showed that there is an effect of Digital Transformation the job stress. Also the study discovered that the Authoritarian Leadership moderated on relationship between Digital Transformation and Job Stress. So the study made some conclusions about how to treat.